The Effect of Implementing Differentiated Based Learning (DBL) on Students' Understanding with Student Learning Style - Wawan Juandi; Ummi Fariqo (Program Pascasarjana Universitas Ibrahimy, 2025)
The objectives of this research are a students' understanding of Akidah Akhlak material is an important aspect in shaping the character and mo rals of students. However, in learning practices, many students still experience difficulties in understanding moral values due to a uniform learning approach that does not consider individual differences. Differences in learning styles, abilities, and interests among students require flexible, adaptive learning strategies that can accommodate such diversity. One approach deemed relevant to address this challenge is Differentiated-Based Learning (DBL), which tailors learning content, processes, and outcomes to students' characteristics. This research used a quantitative perspective to examine the context of the research. Data collection in this research is carried out by observations, documentation, and interviews, angket, pretest and post test.